Detecting sub-instability before three Mw > 6.0 earthquakes on Chinese mainland in 2020–2022 with load/unload response ratio - Huaizhong Yu; Donghui Jia; Chieh-Hung Chen; Yue Liu; Haitao Wang; Jie Liu; Rui Yan; Binbin Zhao; Jianming Liu; Yuchuan Ma; Guihong Han; Wen Yang; et al. (Geomatics, Natural Hazards & Risk)
The sub-instability refers to a stress state that exists between the maximum stress the rock can withstand and its final failure. This stress state should be an indicator of impending large earthquakes, as it occurs in the final stage of earthquake nucleation. We apply the Load/Unload Response Ratio (LURR) method to explore sub-instability in the source media before large earthquakes. The earthquake-related observation data such as the groundwater, crustal deformation, electromagnetism and so on were adopted as data input. The load and unload phases at each observation station are discriminated by the change of Coulomb failure stress caused by earth tides along the tectonically optimal sliding direction. Retrospective studies of this approach on the 2020 Mw6.0 Jiashi, Xinjiang, 2022 Mw6.6 Menyuan, Qinghai, and Mw6.6 Luding, Sichuan earthquakes show that the LURR time series derived from the observation stations near the epicenter exceed 2 standard deviations of the mean within several days to years before the mainshocks. Additionally, as the time of mainshock approaches, the distance between the stations detecting LURR anomaly and epicenter decreases. The LURR anomalies indicate the presence of sub-instability prior to a large earthquake, and their spatio-temporal evolution may suggest the weakening processes in the source media.